Ground investigations for Changi east reclamation projects - Bo, Myint Win (2013)
Geotechnical ground investigation is important in all construction works particularly, land reclamation projects. The Changi East reclamation project is a mega project that involves creation of land space as large as 3,000 hectares in multiple phases between 1991 and 2005. Ground investigation plays a critical role in the Changi project which involved substantial amount of ground improvement works after reclamation by sand filling. One important aspect of the investigation was to evaluate the geotechnical characteristics of the underlying compressible soils beneath the original seabed for the selection of suitable methods of ground improvement. The other important aspect of the investigation was to characterize and verify the compactness of the reclaimed sand fill. Many types of in situ tests were extensively used in the project. The field vane shear test provides correlations between the undrained shear strength and depth for the upper and the lower marine clay strata in the Northern part and the Southern Part of the reclaimed site. Combined with laboratory undrained shear strength tests, the field vane strength profiles allow the derivation of the undrained shear strength over effective stress ratios for the upper and the lower marine clays. In addition, results from three other in situ tests, the piezocone cone penetration test, the flat dilatometer test, and the self boring pressuremeter test provided useful verification of these correlations. A field-performance based method of assessing degree of consolidation in the underlying clay was developed by combining field monitoring, laboratory testing and conventional as well as specialized in situ testing. An effective use of in situ testing methods for assessment, the outcome of ground improvement and for fill quality control in the densification of granular soils is illustrated with field observation data collected at the project site.